Evidence of recent interspecies horizontal gene transfer regarding nucleopolyhedrovirus infection of Spodoptera frugiperda - Barrera, Gloria Patricia (2015)
Background: Baculoviruses are insect-associated viruses carrying large, circular double-stranded-DNA genomes with significant biotechnological applications such as biological pest control, recombinant protein production, gene delivery in mammals and as a model of DNA genome evolution. These pathogens infect insects from the orders Lepidoptera, Hymenoptera and Diptera, and have high species diversity which is expressed in their diverse biological properties including morphology, virulence or pathogenicity. Spodoptera frugiperda (Lepidoptera: Noctuidae), the fall armyworm, represents a significant pest for agriculture in America; it is a host for baculoviruses such as the Spodoptera frugiperda multiple nucleopolyhedrovirus (SfMNPV) (Colombia strain, genotype A) having been classified as a Group II alphabaculovirus making it a very attractive target for bioinsecticidal use. Results: Genome analysis by pyrosequencing revealed that SfMNPV ColA has 145 ORFs, 2 of which were not present in the other sequenced genotypes of the virus (SfMNPV-NicB, SfMNPV-NicG, SfMNPV-19 and SfMNPV-3AP2). An in-depth bioinformatics study showed that ORF023 and ORF024 were acquired by a recent homologous recombination process between Spodoptera frugiperda and Spodoptera litura (the Oriental leafworm moth) nucleopolyhedroviruses. Auxiliary genes are numerous in the affected locus which has a homologous region (hr3), a repetitive sequence associated with genome replication which became lost in SfColA along with 1 ORF. Besides, the mRNAs associated with two acquired genes appeared in the virus? life-cycle during the larval stage. Predictive studies concerning the theoretical proteins identified that ORF023 protein would be a phosphatase involved in DNA repair and that the ORF024 protein would be a membrane polypeptide associated with cell transport. Conclusions: The SfColA genome was thus revealed to be a natural recombinant virus showing evidence of recent horizontal gene transfer between different baculovirus species occurring in nature. This feature could be the cause of its high insecticidal power and therefore SfColA becomes a great candidate for bioinsecticide formulations.